2020
DOI: 10.1155/2020/5109841
|View full text |Cite
|
Sign up to set email alerts
|

Mathematical Modeling, Analysis, and Optimal Control of Corruption Dynamics

Abstract: In this paper, a nonlinear deterministic model for the dynamics of corruption is proposed and analysed qualitatively using the stability theory of differential equations. The basic reproduction number with respect to the corruption-free equilibrium is obtained using next-generation matrix method. The conditions for local and global asymptotic stability of corruption-free and endemic equilibria are established. From the analysis using center manifold theory, the model exhibits forward bifurcation. Then, the mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 15 publications
0
16
0
1
Order By: Relevance
“…In this study, a deterministic mathematical model with optimal control for the dynamics of MSV was formulated and analyzed to find the best strategy for controlling MSD in maize population. We derived and analyzed the necessary conditions for optimal control strategies using Pontryagin’s maximum principle ( Hugo et al., 2019 ; Alemneh, 2020 ). With the principle, we obtained the Hamiltonian, the adjoin variables, the characterization of the controls and the optimality system.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, a deterministic mathematical model with optimal control for the dynamics of MSV was formulated and analyzed to find the best strategy for controlling MSD in maize population. We derived and analyzed the necessary conditions for optimal control strategies using Pontryagin’s maximum principle ( Hugo et al., 2019 ; Alemneh, 2020 ). With the principle, we obtained the Hamiltonian, the adjoin variables, the characterization of the controls and the optimality system.…”
Section: Discussionmentioning
confidence: 99%
“…In order to achieve this, the following objective functional is considered: where t f is the final time, d 1 and d 2 are balancing constant coefficients of the infected maize and infected leafhopper respectively while w 1 , w 2 and w 3 are weight coefficients for each individual control measure. We choose a nonlinear cost on the controls based on the assumption that the cost takes nonlinear form ( Alemneh, 2020 ; Alemneh et al., 2020 ; Osman et al., 2020a ). The goal is to find the optimal control triple ( , ) such that: where the control set is measurable on [0, t f ], .…”
Section: Existence Of Optimal Controlmentioning
confidence: 99%
“…e group accounts for one-third of the 44,789 new HIV adult infections in 2017. National AIDs and STIs Control Programme (NASCOP) 2018 [4] estimates show that 105,230 adolescents between 10-19 years were living with HIV; in addition, 184,700 young adults (15)(16)(17)(18)(19)(20)(21)(22)(23)(24) are also infected. Sadly, the data indicates that adolescents account for one in every 10 AIDS-related deaths.…”
Section: Introductionmentioning
confidence: 99%
“…It was also shown that the corruption endemic equilibrium is locally asymptotically stable provided that the basic reproduction number is greater than one. In [15], the author developed an epidemiology model for the corruption dynamics. Furthermore, he extended the model to include optimal control with combinations of two corruption preventive measures, namely, (i) campaigning about corruption through media and advertisement and (ii) exposing the corrupted individuals to jail and giving punishment.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation